Thermal and morphological characterization of poly(vinyl alcohol) based phenylboronic acid hybrid nanofibers: the effect of experimental parameters on the nanofiber diameter - (:unkn) unknown (MAIK NAUKA/INTERPERIODICA/SPRINGER, 2015)
The aim of this study was to prepare and characterize phenylboronic acid/poly(vinyl alcohol) composite nanofibers. The effects of solution properties and processing parameters on the structure and morphology of the nanofibers were thoroughly investigated. The structure and morphology of nanofibers were examined by SEM, DSC, and FTIR spectroscopy. The nanofiber diameter and the nanostructured morphology depended on solution viscosity, applied electric voltage and tip-to-collector distance. The combination of different materials and processing parameters could be used to fabricate bead-free composite nanofibers. It was found that the solution viscosity have relatively larger effects on the fiber diameter than the other parameters. The thermal properties of polyvinyl alcohol and polymer composite nanofibers were investigated. The analysis revealed that composite containing nanofibers gave higher char yield compared to poly(vinyl alcohol) nanofiber.
Keywords: AQUEOUS-SOLUTIONS; MATS; COMPOSITE